2001
DOI: 10.1105/tpc.13.4.979
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sequence Analysis Reveals Extensive Microcolinearity in the Lateral Suppressor Regions of the Tomato, Arabidopsis, and Capsella Genomes

Abstract: A 57-kb region of tomato chromosome 7 harboring five different genes was compared with the sequence of the Arabidopsis genome to search for microsynteny between the genomes of these two species. For all five genes, homologous sequences could be identified in a 30-kb region located on Arabidopsis chromosome 1. Only two inversion events distinguish the arrangement of the five genes in tomato from that in Arabidopsis. Inversions were not detected when the arrangement of the five Arabidopsis genes was compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 31 publications
6
72
2
Order By: Relevance
“…Microsynteny analysis between the chromosomal segments harboring the LATERAL SUPPRESSOR genes in tomato and Arabidopsis has demonstrated that both genes are orthologous (Rossberg et al 2001). However, the LATERAL SUPPRESSOR proteins of both species show only 50.5% identity.…”
Section: Lateral Suppressor Function Is Conserved During Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsynteny analysis between the chromosomal segments harboring the LATERAL SUPPRESSOR genes in tomato and Arabidopsis has demonstrated that both genes are orthologous (Rossberg et al 2001). However, the LATERAL SUPPRESSOR proteins of both species show only 50.5% identity.…”
Section: Lateral Suppressor Function Is Conserved During Evolutionmentioning
confidence: 99%
“…AC005223), which both contain the most homologous LATERAL SUPPRESSOR gene (At1g55580). Microsynteny studies between the tomato Ls region and the identified BAC clones demonstrated that the gene repertoire within this region is completely conserved, but two inversions distinguish the arrangements of genes in both species (Rossberg et al 2001). These results demonstrate that the isolated DNA segment contains the Ls-orthologous gene from Arabidopsis (LAS).…”
mentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genome.cshlp.org Downloaded from 2001a) even for species that are thought to have diverged from Arabidopsis as much as 100 Mya or more (Paterson et al 1996;Ku et al 2000;Mayer et al 2001;Rossberg et al 2001;Salse et al 2002) based largely on sequenced BACs or other large DNA fragments. However, to the degree that gene loss followed polyploidization events in these lineages, these studies chronically underestimated the degree of conserved synteny that existed Kellogg 2003).…”
Section: Genome Research 1203mentioning
confidence: 99%
“…A pattern of chromosomal colinearity has been identified between Arabidopsis and other flowering plants (Grant et al 2000;Rossberg et al 2001). Genomic synteny has been found to be well conserved among a broad array of species, even though genomic size in plant exhibits a wide diversity, e.g., 125 Mb for A. thaliana to 125 Gb for Fritillaria assyriaca (Bennett and Smith 1976).…”
mentioning
confidence: 99%